"I often find myself now basing my analysis very much on what Kalecki himself wrote sixty or seventy years ago". Interview with Malcolm Sawyer - Malcolm Sawyer (Intervention. European Journal of Economics and Economic Policies, 2012)
First paragraph: Malcolm, our first set of questions is about your career in retrospective. You have been a professional economist for more than 40 years. What was your motivation to become an economist, how did you get in contact with heterodox economics and what were the major steps in your career as a professional economist?
Keywords: 330